Practices and Attitudes of Dental Loupes and Their Relationship to Musculoskeletal Disorders among Dental Practitioners - Khalid Aboalshamat; Ola Daoud; Lina Ayman Mahmoud; Sakina Attal; Rahaf Alshehri; Duaa Bin Othman; Reem Alzahrani (International Journal of Dentistry)
Objective. A dental loupe is a tool used by many dentists and dental students to improve visual field and performance. This study aims to assess the practices and attitudes about dental magnification loupes and their relationship to musculoskeletal disorders. Materials and Methods. A cross-sectional study was conducted involving 400 dental students and dentists in four dental colleges in Jeddah, Saudi Arabia. The mean age was 28.35 years (SD = 8.50), and 56% of the participants were male. Also, 70.75% were students or interns, while 29.25% were dentists. Data gathering was conducted using a questionnaire that was composed of four sections: demographic, magnification devices usage, attitude toward dental loupes, and the Nordic questionnaire to assess musculoskeletal disorders. Results. A total of 66% of participants had used dental magnification tools before, but only 12.25% were using dental loupes at the time of the study. The main reported advantages of dental loupes were comfort in vision (59.25%) and improved work accuracy (53%), while the main disadvantage was difficulty in visual measurement (28.5%). A total of 73.25% reported that price was the main barrier to the use of dental loupes. Lower back (63.5%), neck (65.25%), and shoulder (46.25%) pain were the most frequently reported areas of discomfort. There was a significant relationship (<0.05) between the use of dental loupes and lowered levels of reported discomfort in the lower back, neck, shoulders, elbows, upper back, and feet. Conclusion. There are few dental professionals who use dental loupes in Saudi Arabia. There was a significant relationship between dental loupes use and reduction of musculoskeletal disorders among dental students and dentists.